Powers of the President as Chief Executive in Determining the Number of State Ministries Based on the 1945 Constitution - Mustomi, Otom; Siregar, Hamdan Azhar (UNIVERSITAS PAKUAN, 2023)
Powers of the President as Chief Executive in Determining the Number of State Ministries According to the 1945 Constitution. With the amendments to the 1945 Constitution, the President and his partner, namely the Vice President, are directly elected by the people. And the pair that gets the most votes will be sworn in as President and Vice President. Thus began a new chapter in a government led by the President and Vice President. In addition to the President being assisted by the Vice President, based on article 17 paragraph (1) of the 1945 Constitution